Morphology of spinal ganglia of different segmentary levels in the domestic dog - L. P. Horalskyi; N. L. Kolesnik; I. M. Sokulskiy; S. I. Tsekhmistrenko; O. F. Dunaievska; I. Y. Goralska (Regulatory Mechanisms in Biosystems, 2020)
The spinal ganglia, which perform the function of the first link on the afferent impulses’ way from the receptors to the central nervous system, recognize internal and external irritations, and are the first to transform them into a nervous impulse. As the representatives of the peripheral nervous system, they are some of the main objects of the studies in contemporary neuromorphology. Based on the results of anatomic, neurohistological, histochemical, morphometric and statistical methods of the studies, we conducted a complex survey, revealing the morphology of spinal ganglia of different segmental levels in the domestic dog. In particular, we determined the differences in the microscopic structure and morphometric parameters of cervical, thoracic, lumbar and sacral spinal ganglia and the ganglia of the cervical and lumbar enlargements in mature domestic dogs. The study showed that the spinal ganglia of domestic dogs can have different skeletotopy, different shape and sizes due to their species peculiarity. Also, the surveyed animals, according to the results of our studies, had the cervical and thoracic spinal ganglia of oval, while the lumbar and sacral – spindle-like shapes. According to the results of morphometry, the area of the spinal ganglia in lengthwise section differed: the smallest area belonged to the thoracic, the largest to the sacral spinal ganglia. The density of neuronal arrangement per 0.1 mm2 of the area of the spinal ganglia correlated with their sizes: the highest parameter was identified for the thoracic spinal ganglia, the lowest – for the sacral. The conducted studies revealed that histo- and cyto-structure of the spinal ganglia is characteristic of notable differentiation of the nervous cells of small sizes. Therefore, we differentiated neurons of the spinal ganglia into large, medium and small. The highest quantity of large neurons was found in the sacral ganglia, and largest amount of medium-sized neurons – in the ganglia of the lumbar enlargement. In other ganglia, small neurons dominated. Correspondingly, different nuclear-cytoplasmic ratio in these neurons was determined, indicating different extent of morphofunctional condition of nervous cells. We determined content of localization and separation of nucleic acids in histostructure of the spinal cord at the tissue and cellular levels.